BALANCE HALAL FOOD SUPPLY CHAIN: A MATHEMATICAL MODEL APPROACH FOR HALAL FOOD SUPPLY CHAIN SUSTAINABILITY - dwi agustina kurniawati (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2018)
As the demand for halal food becomes raising and the supply of halal food is limited, it is required a strategy to optimize the halal food supply chain. The optimization of halal food supply chain can support its sustainability. Therefore, study about halal food supply chain optimization is required. This paper try to develop a mathematical model, entitled as Balance Halal Supply Chain (BHSC) model. This model propose a distribution strategy for halal food supply chain from limited halal slaughterhouses to several halal markets so as the total cost of distribution becomes minimize. It is assumed that all halal market demands must be fulfilled, so the lack ness cost becomes zero. The model try to fulfill all the halal market demands and minimize the oversupply and transportation costs. BHSC is modeled as MILP. Numerical experiment is performed to validate the model and it is solved by CPLEX Solver Version 12.6.3. Based on the experiment result, it is shown that the model can be used by halal supply chain decision maker as the decision making tool to design the best strategy for distributing the limited number of halal meat to many halal markets for its supply chain sustainability. The BHSC model can minimize the total cost of distribution that consists of oversupply and transportation costs, in the case of all halal market demands must be fulfilled. In conclusion, the proposed model becomes an alternative method to support the halal food supply chain sustainability.